2006
DOI: 10.1007/s10719-006-8635-6
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of the potential receptor for wheat germ agglutinin from human neutrophils

Abstract: Neutrophils participate in host protection and central to this process is the regulation of oxidative mechanisms. We purified by affinity chromatography the receptor for the GlcNAc-specific WGA from CD14+ CD16+ cell lysates (WGAr). The receptor is a 141 kDa glycoprotein constituted by two subunits of 78 and 63 kDa. It is mainly composed of Ser, Asx, and Gly, and, in a minor proportion, His, Cys, and Pro. Its glycan portion contains GlcNAc, Gal, and Man; NeuAc and GalNAc were identified in a minor proportion. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…The α 4 β 1 integrin was extracted and purified from HEK293 cells stably expressing the α 4 integrin subunit (these cells endogenously express the β1 integrin subunit: data not shown). The cells were collected with a cell scraper, then membrane proteins were extracted and α 4 β 1 integrin was purified by affinity chromatography, as described . The binding buffer contained Tris–HCl 25 mM pH 7.5, CaCl 2 1 mM, MgCl 2 1 mM, MnCl 2 1 mM, BSA 2% (w/v), phenylmethanesulfonyl fluoride (PMSF) 1 mM, aprotinin 1 mg/mL, and leupeptin 50 mM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The α 4 β 1 integrin was extracted and purified from HEK293 cells stably expressing the α 4 integrin subunit (these cells endogenously express the β1 integrin subunit: data not shown). The cells were collected with a cell scraper, then membrane proteins were extracted and α 4 β 1 integrin was purified by affinity chromatography, as described . The binding buffer contained Tris–HCl 25 mM pH 7.5, CaCl 2 1 mM, MgCl 2 1 mM, MnCl 2 1 mM, BSA 2% (w/v), phenylmethanesulfonyl fluoride (PMSF) 1 mM, aprotinin 1 mg/mL, and leupeptin 50 mM.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were collected with a cell scraper, then membrane proteins were extracted and α 4 β 1 integrin was purified by affinity chromatography, as described. 68 The binding buffer contained Tris−HCl 25 mM pH 7.5, CaCl 2 1 mM, MgCl 2 1 mM, MnCl 2 1 mM, BSA 2% (w/v), phenylmethanesulfonyl fluoride (PMSF) 1 mM, aprotinin 1 mg/mL, and leupeptin 50 mM. First, we allowed for the slow interaction between the α 4 integrin protein and the rabbit antihuman α 4 integrin antibody by incubating them together for 1 h at 4 °C.…”
Section: Author Contributionsmentioning
confidence: 99%
“…The binding of the peptidomimetics 1e6 to a4b1 integrin was measured by (SPA), using Jurkat cells stably expressing human a4 integrin, and 125 I-FN as the specific radioligand [46,47]. Western blot analysis of the a4b1 integrin, extracted from cell lysate and purified by chromatography, confirmed that both a4 and b1 integrin subunits were present in the eluate employed for the test (S.M.).…”
Section: Scintillation Proximity-binding Assaymentioning
confidence: 91%
“…Specific binding of 125 I-FN to an antibody-captured a4 and b1 integrin was time-dependent; the signal reached a plateau in 10 h and remained constant for the rest of the 24 h incubation (S.M.). The relatively slow kinetics of the SPA may require the establishment of equilibrium between the different components [46,47]. 125 I-FN specific binding to the SPA bead-associated a4b1 integrin, measured after overnight incubation, was inhibited in a concentration-dependent manner by BIO1211, MPUMP-Leu-Asp-Val-Pro-OH (1), with IC 50 and Ki values of 4.8 and 1.5 nM, respectively (Table 1).…”
Section: Scintillation Proximity-binding Assaymentioning
confidence: 99%
“…We also explored an alternative LED excitation light source to improve the excitation efficiency of the APC fluorochrome, as opposed to the mercury arc lamp which is used as a light source in the CellTracks [ 12 ]. In addition, wheat germ agglutinin (wga), a lectin that binds to sialic acid and N-acetylglucosamine residues, was explored because it is present on cellular plasma membranes [ 13 , 14 , 15 , 16 , 17 , 18 ]. We examined the presence of a cell membrane by using wga conjugated to AlexaFluor-488 and adding it to the CellSearch immunostaining cocktail.…”
Section: Introductionmentioning
confidence: 99%